BIOLOGICAL PERSPECTIVES IN THE STUDY OF EMOTION - Palmero Cantero, Francisco (Anales de Psicología / Annals of Psychology)
This paper offers a diachronic perspective of the biological approaches in Psychology of Emotion. So, from the classical theories of James and Cannon, solidly based on the evolutionists criteria, to more actual biological homeostatic appreciation, some of the more relevant formulations are considered. In this revision is emphasised the subcortical localisation of structures that directly participate in emotional processes. Moreover, the differential implication of each hemisphere is relevant. Originally, authors thought simply that the left brain was the seat of the reason and that the right brain was the seat of the emotion. But we now know that this relation is more complex. Posed versus spontaneous emotions may be guided by different parts of the brain.